Active neurocysticercosis at the Hospital for Tropical Diseases, London: a clinical case series. (3rd July 2018) - Hunter, Ewan; Cliff, Michael; Armstrong, Margaret; Manji, Hadi; Jäger, Hans Rolf; Chiodini, Peter; Brown, Mike
Abstract: Background: Neurocysticercosis is the commonest infectious cause of epilepsy in endemic countries, and accounts for a greater number of cases worldwide than any other single pathology. Infection is associated with long-term exposure in low-income countries, although acquisition after travel has been recognized. The standard of care in the UK is inpatient treatment with anti-helminthic drugs and steroids. Methods: The authors reviewed all cases of neurocysticercosis managed at the Hospital for Tropical Diseases in London, England, between 2001 and 2015. Active disease was defined as evidence of either viable cysts or involuting cysts with associated parenchymal inflammation. Results: Of 26 active cases, 65.4% were migrants from nine different countries; 34.6% were UK-born travellers who had visited 19 countries across South and Central America, sub-Saharan Africa, South and South-east Asia; India was the commonest country of exposure in both groups. Only 73.1% presented with seizures; two diagnoses were made through brain imaging of patients with peripheral cysticerci; 53.8% had a single cyst. Migrants were more likely to be seropositive than travellers (p=0.033). Only two patients had seizures during admission, one of whom had multiple seizures prior to diagnosis. Conclusions: Neurocysticercosis presents in a non-endemic setting in both migrants and travellers. Travellers are less likely to be sero-positive. Not all cases of neurocysticercosis present with seizures. Outpatient management could be considered for selected patients.